Unsupervised assessment of cognition in the Healthy Brain Project: Implications for web‐based registries of individuals at risk for Alzheimer's disease. Issue 1 (26th June 2020) - Perin, Stephanie; Buckley, Rachel F.; Pase, Matthew P.; Yassi, Nawaf; Lavale, Alexandra; Wilson, Peter H.; Schembri, Adrian; Maruff, Paul; Lim, Yen Ying
Abstract: Introduction: Web‐based platforms are used increasingly to assess cognitive function in unsupervised settings. The utility of cognitive data arising from unsupervised assessments remains unclear. We examined the acceptability, usability, and validity of unsupervised cognitive testing in middle‐aged adults enrolled in the Healthy Brain Project. Methods: A total of 1594 participants completed unsupervised assessments of the Cogstate Brief Battery. Acceptability was defined by the amount of missing data, and usability by examining error of test performance and the time taken to read task instructions and complete tests (learnability). Results: Overall, we observed high acceptability (98% complete data) and high usability (95% met criteria for low error rates and high learnability). Test validity was confirmed by observation of expected inverse relationships between performance and increasing test difficulty and age. Conclusion: Consideration of test design paired with acceptability and usability criteria can provide valid indices of cognition in the unsupervised settings used to develop registries of individuals at risk for Alzheimer's disease.